Avian haemosporidians of breeding birds in the Davis Mountains sky-islands of west Texas, USA - Viridiana Martinez; Katrina D. Keith; Jacquelyn K. Grace; Gary Voelker; L. C. Ranford-Cartwright (Parasitology, 2023)
Avian haemosporidians are protozoan parasites transmitted by insect vectors that infect birds worldwide, negatively impacting avian fitness and survival. However, the majority of haemosporidian diversity remains undescribed. Quantifying this diversity is critical to determining parasite–host relationships and host-switching potentials of parasite lineages as climate change induces both host and vector range shifts. In this study, we conducted a community survey of avian haemosporidians found in breeding birds on the Davis Mountains sky islands in west Texas, USA. We determined parasite abundance and host associations and compared our results to data from nearby regions. A total of 265 birds were screened and infections were detected in 108 birds (40.8%). Most positive infections were identified as Haemoproteus (36.2%), followed by Plasmodium (6.8%) and Leucocytozoon (0.8%). A total of 71 haemosporidian lineages were detected of which 39 were previously undescribed. We found that regional similarity influenced shared lineages, as a higher number of lineages were shared with avian communities in the sky islands of New Mexico compared to south Texas, the Texas Gulf Coast and central Mexico. We found that migratory status of avian host did not influence parasite prevalence, but that host phylogeny is likely an important driver.